Exploring smart city atmospheres: The case of Milton Keynes. Issue 127 (December 2021) - Cook, Matthew; Valdez, Alan-Miguel
Highlights: Affective atmospheres arise from materialities, places and encounters in cities. Atmospheres make some smart futures appear more credible and desirable than others. Actors engage in the deliberate cultivation of smart atmospheres. Atmospheres provide mechanisms of complicity and resistance to smart urbanism. Abstract: Smart cities are rapidly becoming the main form of urban development initiated in response to calls to address certain ills such as unsustainable cities. Often presented as rational responses to such challenges, there are affective dimensions which are political and impact their development in various places. We investigate these affective dimensions by using the concept of atmospheres -collective affects arising from encounters between places, actors, materialities and (hi)stories. Our work builds on the premise that acceptance of smart city initiatives relies on their supporter's ability to disseminate compelling stories about smart urban futures. Atmospheres matter here because the stories that can be credibly told are not arbitrary – to be believed, urban stories must be embedded in and coupled to the materialities and affects of their environment. The aim of this paper is to investigate the deliberate cultivation of atmospheres by actors with urban remits, revealing how such atmospheres can become impactful mechanisms for selectively rendering cities amenable or refractory to different stories about smart urban futures. An in-depth case study of the English new town of Milton Keynes is presented to illustrate how atmospheres have been cultivated to selectively resist or reinforce the stories through which the smart city agenda is advanced. Narratives about rationality and data-driven efficiency were translated into specific versions of the future. The resulting encounters gave rise to atmospheres of reception, anticipation, innovation and progress through which urban spaces were rendered selectively receptive to specific forms of smart development in pursuit of local, contextually defined goals.